2017
DOI: 10.2144/000114617
|View full text |Cite
|
Sign up to set email alerts
|

Western Blot Analysis of Cells Encapsulated in Self-Assembling Peptide Hydrogels

Abstract: Continuous optimization of in vitro analytical techniques is ever more important, especially given the development of new materials for tissue engineering studies. In particular, isolation of cellular components for downstream applications is often hindered by the presence of biomaterials, presenting a major obstacle in understanding how cell-matrix interactions influence cell behavior. Here, we describe an approach for western blot analysis of cells that have been encapsulated in self-assembling peptide hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The main reason for this stickiness is the release of nuclear DNA. Studies have shown that sonication can generate cleavage stress to break down the DNA structure, which dramatically improves the lysis and dissociates the target protein [ 14 , 15 ]. Of course, repeated grinding, pipetting, DNase, or dilution with RIPA and loading buffer (4:1) can also reduce viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for this stickiness is the release of nuclear DNA. Studies have shown that sonication can generate cleavage stress to break down the DNA structure, which dramatically improves the lysis and dissociates the target protein [ 14 , 15 ]. Of course, repeated grinding, pipetting, DNase, or dilution with RIPA and loading buffer (4:1) can also reduce viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for this stickiness is the release of nuclear DNA. Studies have shown that sonication can generate cleavage stress to break down the DNA structure, which dramatically improves the lysis and dissociates the target protein [14,15]. The efficiency of PVP-40 blocking for 10 min was comparable to that of skim milk for 1 h. The experimental procedure was the same as the standard experimental procedure except for the blocking reagents (n = 6).…”
Section: Discussionmentioning
confidence: 99%
“…Total protein was isolated from a part of the separated ventricular portion of the isolated heart tissue by a method described by Burgess et al, 22 with slight modifications. The peptide separation gradient of 75 minute was performed according to a method described by Kumari et al 23 The functional annotation of the rat heart proteins was performed using Blast2GO 24 .…”
Section: Methodsmentioning
confidence: 99%
“…These synthetic hydrogels were enzymatically crosslinked, and their dissociation to release the embedded cell colonies was achieved by enzymatic digestion. Others have successfully isolated proteins and/or RNA from cells embedded in agarose hydrogels (Wang et al, 2009), agarose-collagen hydrogels (Cambria et al, 2020), chitosan-based hydrogels (Yu et al, 2013), or self-assembled peptide hydrogels (Burgess et al, 2017). Finally, Sawicki et al proposed an approach to isolate proteins secreted into the microenvironment by first decellularizing the sample and then enzymatically degrading the PEG hydrogel, cross-linked by collagenase-degradable cross-linkers.…”
Section: Commentary Background Informationmentioning
confidence: 99%